2019
DOI: 10.3389/fpls.2019.00473
|View full text |Cite
|
Sign up to set email alerts
|

Proteases Underground: Analysis of the Maize Root Apoplast Identifies Organ Specific Papain-Like Cysteine Protease Activity

Abstract: Plant proteases are key regulators of plant cell processes such as seed development, immune responses, senescence and programmed cell death (PCD). Apoplastic papain-like cysteine proteases (PL) are hubs in plant-microbe interactions and play an important role during abiotic stresses. The apoplast is a crucial interface for the interaction between plant and microbes. So far, apoplastic maize PL and their function have been mostly described for aerial parts. In this study, we focused on apoplastic PLCPs in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…pL1M-F1-LpCP1::2×35S was amplified from LpCP1 (maker-scaffold_2516|ref0039699-exonerate_est2genome-gene-0.3) leaving out the DNA sequence coding for the granulin domain. pL1M-F1-CP1Amut-nogran-mCherry::2×35S is described in Schulze Hüynck et al , 2019. The DNA fragments were ligated as previously described in Weber et al , 2011 and transformed first into E. coli Top10 competent cells and then into A. tumefaciens GV3101 competent cells for overexpression in N. benthamiana .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…pL1M-F1-LpCP1::2×35S was amplified from LpCP1 (maker-scaffold_2516|ref0039699-exonerate_est2genome-gene-0.3) leaving out the DNA sequence coding for the granulin domain. pL1M-F1-CP1Amut-nogran-mCherry::2×35S is described in Schulze Hüynck et al , 2019. The DNA fragments were ligated as previously described in Weber et al , 2011 and transformed first into E. coli Top10 competent cells and then into A. tumefaciens GV3101 competent cells for overexpression in N. benthamiana .…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of N. benthamiana apoplastic fluids was performed as described in Schulze Hüynck et al , 2019. In short, three days post Agrobacterium infiltration N. benthamiana leaves were harvested, and vacuum infiltrated with MilliQ water three times for 5 min at 60 mbar with a 2 min interval of atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ziemann et al [185] pointed out that Zip1 peptide, which is released in the presence of PLCP, leads to SA accumulation in maize leaves. Moreover, Schulze Hüynck et al [186] identified a specific PLCP named CP1C in maize root. Surprisingly, CP1C which shares sequence homology to the Arabidopsis RD21 subfamily did not show higher activity after SA treatment of maize roots.…”
Section: Apoplastic Peptides Related To Plant Defensementioning
confidence: 99%